The challenges in digital learning transformation: An inclusive perspective of Muslim university students - Abd Rahman, Hairulniza; Rahim, Nur Fazliana; Mohd Khushairi, Noor Azreen; Omar, Siti Nur Zahirah (Journal of Islamic, Social, Economics and Development, 2026)
Digital learning transformation has rapidly reshaped higher education, particularly following the global acceleration of online and hybrid learning environments. However, this transformation is not experienced equally across student populations. This study explores the challenges faced by Muslim university students within an inclusive digital learning framework, focusing on technological constraints, digital literacy, financial and socio-cultural factors. The study proposed a conceptual approach supported by recent empirical literature, this paper proposes an integrative framework that highlights disparities affecting Muslim students, particularly those from underprivileged backgrounds. The findings indicate that digital inequities are not merely technical but deeply embedded in socio-economic and cultural dimensions, including religious practices, gender norms, and access to supportive learning environments. The paper contributes to the discourse on inclusive digital transformation by integrating knowledge-sharing and knowledge-transfer perspectives and proposes strategic recommendations for policymakers and higher education institutions.